PEMIKIRAN SOEKARNO TENTANG TRISAKTI; PERSPEKTIF EPISTEMOLOGI KENNETH GALLAGHER - IRMAWANSAH, IKA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The idea of Trisakti has three formulations, namely sovereign in politics, self-sufficient in the economy, culture personality. This study aims to determine the epistemological idea of Trisakti based on the perspective of Kenneth Gallagher. This study will discuss, (1) Structure Trisakti idea (2) The content of idea Trisakti and (3) The relevance of Trisakti idea in Indonesian state life now. This study will use the hermeneutic of method Wilhelm Dilthey. Dilthey hermeneutics based on the philosophy of life that requires an understanding of (Das Verstehen) of historicity and human experience. The idea of Trisakti is the antithesis of colonialism, imperialism and feudalism. The contents idea of Trisakti is independence. Soekarno know about independence as spirit, dynamical state and self-sufficient. In the aspect of existential, the idea of Trisakti born from awareness of past Soekarno to colonialism, imperialism and feudalism. In the aspect of common sense, the idea of Trisakti influenced by nationalism and marxism. In the context of globalization to the present time, in Indonesia state showing the existence of Involvement by class of kapital transnasional in arranging domestic policy. This can menacing to Indonesian. Therefore need to gazing at the idea Trisakti, for the purpose of give way out to build the nation independence.